Perancangan Sistem Pendukung Keputusan Berbasis Website Pada Pemilihan Instrumen Investasi Terbaik Menggunakan Metode TOPSIS - Surono, Anang; Rossena, Bayu Adjie; Kurniawati, Ika (Department of Informatics, Siliwangi University, Indonesia, 2022)
In managing finances there are various ways that can be chosen, such as saving and investing. Investment has long-term and short-term goals and has several types of instruments with each instrument having a promising return. Generation Z is now familiar with matters related to financial technology for their money management field. The lack of literacy among Generation Z in terms of investment raises doubts and even fear in making an investment making it difficult for them to choose or decide on the best investment instrument product. This study aims to help potential investors, especially Generation Z, in choosing the type of investment according to the selection criteria offered, namely Equity Mutual Funds, Money Market Mutual Funds, Crypto, Bonds, and Deposits. The research method used is Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). Topsis is a multicriteria decision making method based on the concept that the best alternative not only has the shortest distance from the positive ideal solution but also has the longest distance from the negative ideal solution. The results of data analysis obtained the best preference values, namely Equity Mutual Funds of 0.75 and Deposits with a value of 0.62. The results of this study are implemented by designing a website-based decision support system using the PHP programming language and MySql database which can help determine the best investment instrument according to user preferences. keywords : Decision Support System, Invesment, MySQL, PHP, TOPSIS